Pembayaran Dengan Media Electronic Money Dalam Hukum Perbankan - Mizana Ramadhan Alhaq; Ali hanafiah selian (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2022)
This study aims to determine the use of E-money, especially in the perspective of Banking Law in Indonesia, and to find out the problems and legal responsibilities that arise in the use of E-money. The research method used in this study is a qualitative research method with a normative and empirical juridical approach. The results of this thesis show that E-Money in the perspective of Banking Law has a strong legal basis because it has been regulated in Law Number 10 of 1998 concerning Banking and other relevant and relevant laws. However, the form of responsibility of the banking sector towards customers who feel disadvantaged in using E-money from the legal theory of liability is very unfair due to the lack of protection for customers so that it is very detrimental to customers. This is proven by the absence of compensation for the loss of the E-money card.